13th World Congress of Food Science &Amp; Technology 2006
DOI: 10.1051/iufost:20060701
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle analysis of the environmental impact of different cabinet designs

Abstract: The design of refrigerated display cabinets greatly affects their subsequent environmental impact. To control this impact, a designer must primarily consider the operating efficiency of a cabinet. However, less account is taken of the materials used to make the cabinet, nor the construction techniques used. These both have a significant effect on the environmental impact of different cabinets outside the use phase of their life cycle. Initial construction impact, remanufacturability and recyclability are all a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Refrigerated cabinets and shelves' embodied carbon, between 280 and 620 kgCO2-eq/m regarding length of display case [44], is not taken into account in this study due to: i) it has been demonstrated that their use phase represents more than 90% of their environmental impacts (approx. 93% [45], 95% [46]) and ii) they may represent less than 0.04% of building's total GWP. Furthermore, the embodied primary energy corresponding to the addition of glass doors would possibly represent less than 2% of the energy savings related [43].…”
Section: Boundaries Of the Systemmentioning
confidence: 99%
“…Refrigerated cabinets and shelves' embodied carbon, between 280 and 620 kgCO2-eq/m regarding length of display case [44], is not taken into account in this study due to: i) it has been demonstrated that their use phase represents more than 90% of their environmental impacts (approx. 93% [45], 95% [46]) and ii) they may represent less than 0.04% of building's total GWP. Furthermore, the embodied primary energy corresponding to the addition of glass doors would possibly represent less than 2% of the energy savings related [43].…”
Section: Boundaries Of the Systemmentioning
confidence: 99%